The Gold of Numbers in Arabic Folklore - E. V. Kukhareva (Концепт: философия, религия, культура, 2020)
The article is devoted to the attitude to various numbers among Arabs and their reflection on the issue in national and Arabic folklore. The cross-cultural oral lore dedicated to numerals is manifested in a pecular way in Arab world, mixing both pre-Islam expressions and those inherited after the Prophet. Veneration or fear of certain numbers, respect or disapproval of others is certainly associated with religious or everyday views, centuries-old traditions, mundane usages and experience of peoples, who, in turn, live in certain regions with various natural conditions, cultural and ethnic environment. This paper outlines major narratives existing in various regions of the Arab world that are connected to numbers – and provides inductive evidence of their common roots on examples of certain numerical expressions. The ideas Arabs shaped in connection with various numbers reflected the mental and cultural foundations, filling everyday human life with additional aspiration. Some pieces of such folklore are considered sacred and can be found in the Qur’an and in the Hadith of the Prophet. Others, no less significant, were fixed in proverbs and sayings – in some of the most stable and unchangeable sources that can help trace back national and supranational ethics, mentality and aesthtics. However, such a research faces challenges concerning the nature and the usage of numerics. While some numbers enjoy a priority value shared interregionally, there are also numeral expressions that are generally difficult to find in the culture of all Arab ethnic groups. Moreover, the proverbial phraseological fund of the Arab peoples tends to focus on some numbers mostly (i.e. one, two, three) and at the same time tends to overlook other numbers. The study draws closer attention to the functions of a range of numbers in the moral and educational sphere, such as promoting popular unity, consolidation, sharing experience of older generations, teching basic communicative principles. As the topic of the research was hardly explored outside the Qur’an studies framework or the historical context, the attempt of a comprehensive outlook on numerics in Arabic folklore the paper takes is innovative.